Thyroid hormone receptor expression during metamorphosis of Atlantic halibut (Hippoglossus hippoglossus) - Galay-Burgos, M. (2014)
Flatfish such as the Atlantic halibut (Hippoglossus hippoglossus) undergo a dramatic metamorphosis that transforms the pelagic, symmetric larva into a benthic, cranially asymmetric juvenile. In common with amphibian metamorphosis, flatfish metamorphosis is under endocrine control with thyroid hormones being particularly important. In this report we confirm that tri-iodothyronine (T3) levels peak at metamorphic climax during halibut metamorphosis. Moreover we have isolated cDNA clones of TR and TR genes and confirmed the presence in halibut of two TR isoforms (representing the products of distinct genes) and two TR isoforms (generated from a single gene by alternative splicing). Real time PCR was used to assess expression of these genes during metamorphosis. TR shows the most dramatic expression profile, with a peak occurring during metamorphic climax.